2022
DOI: 10.1126/scitranslmed.abn4819
|View full text |Cite
|
Sign up to set email alerts
|

Miswiring of Merkel cell and pruriceptive C fiber drives the itch-scratch cycle

Abstract: Itch sensation provokes the scratch reflex to protect us from harmful stimuli in the skin. Although scratching transiently relieves acute itch through activation of mechanoreceptors, it propagates the vicious itch-scratch cycle in chronic itch by further aggravating itch over time. Although well recognized clinically, the peripheral mechanisms underlying the itch-scratch cycle remain poorly understood. Here, we show that mechanical stimulation of the skin results in activation of the Piezo2 channels on Merkel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Using blue light excitation of nociceptive Schwann cells, we observed that polymodal nociceptors were all as strongly activated by blue light as by a supramaximal mechanical stimulus. This finding is especially striking as existing studies on skin cells like Merkel cells and keratinocytes have not demonstrated an equivalence between and optogenetically driven responses to those of natural mechanical stimuli 14 , 16 , 35 , 36 . We found that in contrast to polymodal nociceptors, mechanonociceptors (A-M and C-M fibers), some of which are required for fast mechanical pain 37 , 38 , showed less connectivity and much lower firing rates to blue light compared to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…Using blue light excitation of nociceptive Schwann cells, we observed that polymodal nociceptors were all as strongly activated by blue light as by a supramaximal mechanical stimulus. This finding is especially striking as existing studies on skin cells like Merkel cells and keratinocytes have not demonstrated an equivalence between and optogenetically driven responses to those of natural mechanical stimuli 14 , 16 , 35 , 36 . We found that in contrast to polymodal nociceptors, mechanonociceptors (A-M and C-M fibers), some of which are required for fast mechanical pain 37 , 38 , showed less connectivity and much lower firing rates to blue light compared to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…Our study demonstrates that the TD keratinocytes encompass unique EpSCs that exhibit characteristics of other epidermal lineages and therefore can potentially be manipulated to establish a complex epithelial structure composed of all epidermal appendages. Age-dependent loss of MCs has been linked to alloknesis, a condition where light touch invokes itch (49)(50)(51). Therefore, harnessing the TD's potential to regenerate MCs could be beneficial for alleviating chronic itch.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive scratching causes skin lesions and aggravates the itch, thus making it more severe and chronic. This is called the “itch–scratch cycle”. However, the mechanisms involved in the itch–scratch cycle remain poorly understood. Interestingly, scratching has been found to play an important role in spinal astrogliosis .…”
Section: Central Glial Cells and Itchmentioning
confidence: 99%